The Beneficial Role of Exercise Training for Myocardial Infarction Treatment in Elderly - Xing, Ying; Yang, Si-Dong; Wang, Man-Man; Feng, Ya-Shuo; Dong, Fang; Zhang, Feng (Frontiers in Physiology, 2020)
Worldwide, elderly people have a higher prevalence of myocardial infarction (MI), which is associated with body function aging and a sedentary lifestyle. In addition to medication, exercise training is a well-established supplementary method to prevent and treat cardiovascular diseases (CVD). Substantial evidence has shown the value of different intensity exercise programs in the prevention and treatment of MI, and exercise rehabilitation programs are also applicable to elderly patients with MI. Although exercise rehabilitation programs could significantly improve function, quality of life (QoL), and lower mortality and morbidity for people with MI, such programs are underused because their mechanisms are not accurately elucidated. In order to promote the application of exercise therapy for MI, this review summarizes the benefits and mechanisms of exercise rehabilitation for post-MI patients and provides rationalized proposals for outpatient cardiac rehabilitation.